Pengembangan media poster 3d santri cerdas tangkal skabies (Sakti) terintegrasi nilai thaharah - Izzanti, Sabrina Faza; Rachmawati, Windi Chusniah (Holistik Jurnal Kesehatan, 2025)
Background: Scabies remains a contagious skin disease that frequently occurs in Islamic boarding school environments. Good personal hygiene can help maintain health and prevent the manifestation of diseases, including scabies. In Indonesia, scabies has a high prevalence rate, ranging from 5.6% to 12.95%. Purpose: This study aims to examine the effectiveness of 3D posters in increasing knowledge and motivation about scabies. Methods: The research employed a Research and Development (R&D) method with a pre-experimental approach using a one-group pretest-posttest design. A total of 98 junior high school students from Al-Muflihun Islamic Boarding School participated in this study, selected using a total sampling technique. The research instrument consisted of a closedended questionnaire with 20 items to measure knowledge and 10 items to measure motivation. Results: The 3D poster product received a media feasibility score of 93.3% and a content feasibility score of 96.8%, indicating it is highly suitable for use. The results of the study, following the intervention, revealed a significant effect of health education using 3D posters on students' knowledge and motivation regarding scabies, with a p-value = 0.000 (p < 0.05) based on the Wilcoxon test. Conclusion: The conclusion of this study there was an increase in students’ knowledge after the intervention, from the “moderate” category (57.3%) to the “good” category (94.1%). The students’ motivation in carrying out prevention tended to be in the “high” category (58.8%), with the average score increasing from 30.64 to 35.55. The use of the 3D Poster health promotion media in this study was able to improve the students’ knowledge and motivation.